f(x) = - x² - 6x - 9 calcule o valor de delta.
Soluções para a tarefa
Respondido por
5
delta= B^(2)- 4AC
delta= -6^(2)-4×(-1)×-9
delta = 36-36
delta =0
delta= -6^(2)-4×(-1)×-9
delta = 36-36
delta =0
Respondido por
5
a = -1 , b = - 6 , c = - 9
delta = b² - 4 x a x c
delta = (-6)² - 4 x (-1) x (-9)
delta = 36 - 36
delta = 0
x = -b + 0u -
/ 2 * a
x = -(-6) + ou -
/ -2
x1= 6 + 0 / -2
x1= 6 / -2
x1 = -3
x2 = 6 - 0 / -2
x2 = 6 / -2
x2 = -3
v = {-3,-3}
delta = b² - 4 x a x c
delta = (-6)² - 4 x (-1) x (-9)
delta = 36 - 36
delta = 0
x = -b + 0u -
x = -(-6) + ou -
x1= 6 + 0 / -2
x1= 6 / -2
x1 = -3
x2 = 6 - 0 / -2
x2 = 6 / -2
x2 = -3
v = {-3,-3}
Perguntas interessantes
Português,
11 meses atrás
Matemática,
11 meses atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás